Analisis Nilai-nilai Pendidikan Karakter dalam Kitab Ihya’ ‘Ulum Al-Din dan Relevansinya dengan Pendidikan Agama Islam - M. Jauharul Ma’arif; Ahmad Maulana (LP. Ma'arif Janggan Magetan, 2022)
Education is a coaching and guidance that is carried out by someone on an ongoing basis to students for the implementation of educational goals that require a neverending process throughout human life and things that are very important or meaningful for human life. This study aims to describe the values of character education in the book Ihya ‘Ulum Al-Din by Imam Al-Gazaly and their relevance to Islamic education. This research includes a qualitative approach with the type of library research using books, scientific articles, documents, and the like as secondary data sources, and the book of Ihya ‘Ulum Al-Din as primary data sources, then describes his research analysis in detailed words and sentences. The results show that the values of character education in the book of Ihya’ ‘Ulum Al-Din especially in Juz 1 Chapter of Science that the authors found are as follows: The values of religious character education, honesty, tolerance, responsibility, patience, politeness, curious, generous, likes to read. The values of character education contained in the book Ihya ‘Ulum Al-Din Juz 1 Chapter of Science that the researchers mentioned above are very relevant to the context of Islamic Religious Education, especially formal educational institutions.